Insecurity and Socio-Economic Development in Ukum Local Government Area, Benue State - Shaibume, Benjamin; Ayangealu, Kingsley Ushahemba (Kashere Journal of Politics and International Relations, 2025)
Nigeria's security woes, especially since the advent of democracy in 1999 to date, could be analyzed from a variety of theoretical standpoints. Thus, this can be attributed to seemingly multitudes of systemic challenges responsible for the present security fiasco in Nigeria. The general insecurity and the threat of it have continued to overwhelm the socio-economic and political process to the extent that security issues have remained a fundamental challenge to successive governments and the people of the country. This paper examines the effects of insecurity on the socio-economic development of the Ukum Local Government Area. Data for this study were collected through the distribution of 200 well-structured questionnaires to Ukum residents. Data collected were analyzed and presented in tables, percentages, and charts. The paper adopted Per-Olof Wikström's Situational Action Theory (SAT) as its framework of analysis to explain the issues under study. The findings reveal that insecurity in Ukum is primarily driven by poverty and high unemployment rates, among other factors. The study also highlights that insecurity has adversely affected the residents' livelihoods, turning many into internally displaced persons (IDPs), disrupting businesses, and causing destruction to properties and lives. The paper recommends increased monitoring, and surveillance of the Nigerian borders by the security agencies, addressing corruption, improving governance, and creating job opportunities to alleviate poverty and address the root causes of insecurity.